Understanding Digital Signal Processing - Gazi, Orhan; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book explains digital signal processing topics in detail, with a particular focus on ease of understanding. Accordingly, it includes a wealth of examples to aid in comprehension, and stresses simplicity. The book is divided into four chapters, which respectively address the topics sampling of continuous time signals; multirate signal processing; the discrete Fourier transform; and filter design concepts. It provides original practical techniques to draw the spectrum of aliased signals, together with well-designed numerical examples to illustrate the operation of the fast transforms, filter algorithms, and circuit designs. Readers of this book should already have some basic understanding of signals and transforms. They will learn fundamental concepts for signals and systems, as the focus is more on digital signal processing concepts rather than continuous time signal processing topics.
Sampling of Continuous Time Signals -- Multirate Signal Processing -- Discrete Fourier Transform -- Analog and Digital Filter Design.
Keywords: Signal processing; Fourier analysis; Measurement; Measuring instruments; Signal, Speech and Image Processing; Fourier Analysis; Measurement Science and Instrumentation